2015
DOI: 10.1002/ange.201410043
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Acetal Hydrolysis by Remote Alkoxy Groups: Evidence for Electrostatic Effects on the Formation of Oxocarbenium Ions

Abstract: In contrast to observations with carbohydrates, experiments with 4‐alkoxy‐substituted acetals indicate that an alkoxy group can accelerate acetal hydrolysis by up to 20‐fold compared to substrates without an alkoxy group. The acceleration of ionization in more flexible acetals can be up to 200‐fold when compensated for inductive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…[26] An epoxide product (10 c) was isolated in 67 %y ield proceeding through two separate steps (Scheme 5b). [27] Overall, the results using this catalytic system are synthetically relevant and are comparable to the state-of-the-art in radical-based intermolecular dehydrogenation reactions.…”
Section: Resultssupporting
confidence: 55%
“…[26] An epoxide product (10 c) was isolated in 67 %y ield proceeding through two separate steps (Scheme 5b). [27] Overall, the results using this catalytic system are synthetically relevant and are comparable to the state-of-the-art in radical-based intermolecular dehydrogenation reactions.…”
Section: Resultssupporting
confidence: 55%
“…Thus, important issues involve the possible involvement of fused and bridging ions versus that of glycosyl oxocarbenium ions and/or reactive intermediates such as glycosyl triflates in the transition state for glycosidic bond formation, with evidence presented both for, and against, dependent on the system and conditions under study. 177,178,[221][222][223][224][225][226][227][228][229] This delicate balance between stereodirecting participation and alternative mechanisms is a prominent feature of the involvement of esters in glycosylation and apparent from the comparison of a recent study on 1,2-trans-glycosylation directed by the presence of 2-O-alkoxymethyl methyl groups, 230 and one of the many instances of intramolecular aglycone delivery, 231 a common strategy for 1,2-cis glycoside formation (Scheme 31). [232][233][234]…”
Section: Participation By Other Functional Groupsmentioning
confidence: 99%
“…110–112 Our studies of reactions of alkoxy-substituted acetals showed that the presence of an alkoxy group, which is inductively electron-withdrawing, can accelerate acetal hydrolysis if it can approach the developing carbocationic carbon atom (Scheme 54 ). 113 114 The rate acceleration trends in hydrolysis were also observed for solvolysis of tosylates (Scheme 55 ). The acceleration is higher than one sees with acyloxy groups, suggesting that alkoxy groups are more participating, likely because their inductive-withdrawing ability is lower.…”
Section: Neighboring-group Participation Is Not As Simple As It Seemsmentioning
confidence: 84%